2000
DOI: 10.1038/sj.onc.1203459
|View full text |Cite
|
Sign up to set email alerts
|

A new predictive factor for hepatocellular carcinoma based on two-dimensional electrophoresis of genomic DNA

Abstract: Molecular genetic analyses have clari®ed that accumulation of genomic changes provides important steps in carcinogenesis and have identi®ed a number of valuable genetic markers for certain cancers. To date, however, no prognostic markers have been identi®ed for hepatocellular carcinoma (HCC). In this study, we used restriction landmark genomic scanning (RLGS), a new high-speed screening method for multiple genomic changes, to detect unknown genetic alterations in HCC. Thirty-one HCC samples and their normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…We have reported that the di erence between non-cancerous liver tissue and HCC in the number of altered RLGS spots was signi®cantly correlated with postoperative disease recurrence. This had been found to be a more useful marker for HCC prognosis than the conventional factors, as documented in our previous report (Itano et al, 2000). This is interpreted to imply that such markers re¯ect genomic changes more closely associated with the actual process of hepatocarcinogenesis than the changes detected by conventional methods.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We have reported that the di erence between non-cancerous liver tissue and HCC in the number of altered RLGS spots was signi®cantly correlated with postoperative disease recurrence. This had been found to be a more useful marker for HCC prognosis than the conventional factors, as documented in our previous report (Itano et al, 2000). This is interpreted to imply that such markers re¯ect genomic changes more closely associated with the actual process of hepatocarcinogenesis than the changes detected by conventional methods.…”
Section: Introductionmentioning
confidence: 72%
“…Global DNA hypomethylation has been frequently observed in many types of cancers and is correlated with prognostic factors in several of these Kim et al (1994); Cravo et al (1996); Soares et al (1999) and Shen et al (1998) reported that decreased levels of global DNA methylation in HCC are correlated with tumor characteristics. In our previous paper we showed that the number of altered RLGS spots in HCC compared to non-cancerous liver tissue was signi®cantly correlated with postoperative recurrence of HCC (Itano et al, 2000), and here we show that the intensity of the HTRS and CNIC spots, in other words, the degrees of demethylation in HTRS and CNIC, were signi®cantly correlated with the number of altered RLGS spots (Figure 3a,b). The above considerations strongly suggest that the number of altered RLGS spots and demethylation in repetitive sequences might be correlated with global DNA hypomethylation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thirteen out of 16 patients whose tumors showed 16 or greater changes in their RLGS profiles had recurrence, while only two out of 15 patients whose tumors showed 12 or less changes recurred. Furthermore, the number of RLGS profile changes was more predictive than the three previously used prognostic indicators (Itano et al, 2000).…”
Section: Development Of Biomarkersmentioning
confidence: 97%
“…However, it is not uncommon for recurrence to occur in patients who are negative for all three of these factors. After RLGS analysis was performed on 31 HCC tumors and corresponding normal tissues, correlations were studied between RLGS profile changes and post-operative recurrence (Itano et al, 2000). Post-operative recurrence correlated significantly with 16 or more RLGS spot changes including both hypo-and hypermethylation events.…”
Section: Development Of Biomarkersmentioning
confidence: 99%